1996
DOI: 10.1016/0040-4020(96)00712-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized cyclopropanes by MIRC reactions of aziridinyl-methylenemalonates

Abstract: The synthesis of cyclopropane derivatives via a MIRC reaction of azidirinyl-methylenemalonates is described. In this way it is possible to introduce a hydrogen, a phenylthio, a tributylstannyl and an olefinic function at the cyclopropane ring, that further contains an alkylamino substituent, Addition of CuCN catalyzed Grignard reagents gave the most promising results. The diastereoselectivity was dependent on the aziridine nitrogen substituent and the bulkiness of the reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The best results were obtained with alkylmagnesium halides in the presence of 10 mol% of copper(I) cyanide (Scheme 10) [15]. A similar MIRC reaction was performed with oxiranyl derivatives [17].…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…The best results were obtained with alkylmagnesium halides in the presence of 10 mol% of copper(I) cyanide (Scheme 10) [15]. A similar MIRC reaction was performed with oxiranyl derivatives [17].…”
Section: Methodsmentioning
confidence: 92%
“…It was shown that the corresponding cis-aziridinyl-methylene malonates produce predominantly the trans cyclopropane product. The stereochemical course of this MIRC reaction was explained [15] by invoking Yamamoto's model for conjugate additions of cyanocuprates to ␥-alkoxy-␣,␤-unsaturated esters [16].…”
Section: (Scheme 2)mentioning
confidence: 99%
See 3 more Smart Citations